RUSSELL’S APPROXIMATION METHOD DAN IMPROVED VOGEL’S APPROXIMATION METHOD DALAM PENYELESAIAN MASALAH TRANSPORTASI - DEWI, NI PUTU INTAN PUSPA; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p251, 2019)
Distribution activities in company which related in distribution sometimes have a problems, one of the problems is transportation problem. To solve that problem can be used a transportation model to obtain the distribution route so the cost that come out is more minimum. The aim of this research is to compare the initial solution of RAM and IVAM and to know the distribution route in distribution of bottled water in the CV. Prasarana Fortuna Prima so obtained the minimum distribution costs after optimality test using MODI. The results showed that RAM gave a lower initial solution than IVAM and the initial solution of RAM was optimum after optimality test using MODI with a distribution routes is from depo Klungkung to Toko Bintang, Toko Subur, Toko Cahaya Melati, Toko Mawar Sari, and Coco Mart Ubud, from depo Kapal to CV. Sumber Jaya, Toko Sol Mandala, and Toko Kayana, from depo Mahendradatta to Toko Sinar Wangi and Toko Aris.